PENGUSAHAAN TERUMBU KARANG SECARA BERKELANJUTAN (Studi Kasus Perubahan Usaha Terumbu Karang Alam ke Budidaya Terumbu Karang di Pulau Serangan, Kccamatan Denpasar Selatan, Kota Denpasar-Bali) - ARSONETRI ARSONETRI (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2011)
Illegal coral extraction (taking coral from nature) as an unsustainable effort affected the degradation of coral reef ecosystem and coastal environment. However, 1t continually happens in Indones1a, particularly in Scr,rngan Island, Bali. The stakeholder in coral extraction effort have gamed good advantages (benefits) making a legally and sustainable clTort such as coral culture still difficult. This study 1s specifically examines the methods of coral culture 1s better and profitable than the methods of coral extraction from nature. Thus, encouragmg all parlles involved (stakeholder), especially fishem1an to apply the coral culture. The research is observed and compared between coral extraction from nature fisherman and coral culture fisherman in Serangan Island, the feasibility, benefits and fisherman's perception. It is also explain the role of government toward of coral extraction and culture. 1he result shows the benefit or advantage of coral culture is higher than coral extraction from nature. It demonstrated by NPV (Net Present Value) and CBR (Cost Benefit Ratio) of coral culture is higher than coral extraction from nature. Therefore, coral culture is economically feasible to replace coral extraction from nature. The fisherman's perception is very pos1llve regarding coral culture effort and implementation replacing coral extraction from nature. In this effort, the government's role is very important in provision mcentive such as modal and subs1d1es, trainings and increasing fisherman capacity building, market insurance, and easier to obtain permits of coral culture.